Understanding Ontario Elementary Teachers' Experience of Interdisciplinary Education Through an Integrative Lens - Hoang, Linh (Université d'Ottawa | University of Ottawa, 2024)
Interdisciplinary education equips young minds with the critical, multi-perspective, and global thinking needed to tackle the vast challenges of the modern world. In Ontario, while the Ministry of Education encourages interdisciplinary education, it lacks clear implementation guidelines and has made budget cuts resulting in the cancellation of many long-standing interdisciplinary programs. This study uses a qualitative approach with a reflexive thematic analysis method to investigate how five elementary Ontario teachers understand and practice interdisciplinary teaching and learning in their classrooms. The study is framed by sociocultural learning theory, using Mansilla's (2017) pragmatic-constructionist interdisciplinary learning model as the analytic lens through which to understand the nature and process of interdisciplinary integration. The findings reveal that participants initiated interdisciplinary education with a focus on students' interests and learning, placing less emphasis on strict adherence to the curriculum. They employed diverse teaching methods, known to facilitate interdisciplinary learning. Consequently, interdisciplinarity emerged organically from student interest and learning; yet it also ultimately enabled teachers to meet curriculum standards. This contradicts curriculum integration literature, which emphasizes the need to develop interdisciplinary units by carefully integrating multiple subjects' contents and purposefully connecting curriculum standards. This literature assumes that starting this way, with planned interdisciplinary units, will lead to effective teaching and learning. By contrast, this study indicates that focusing first on authentic, effective teaching and learning is what fosters interdisciplinarity in elementary schools. The study suggests reassessing curriculum integration frameworks in the direction of more emergent frameworks such as Mansilla's (2017).
Keywords: interdisciplinary education